Excitation energy of 9Be - Pachucki, Krzysztof; Komasa, Jacek (American Physical Society, 2006)
The high precision relativistic and radiative corrections to the energy of the excited 3 S-1 state of the beryllium atom are obtained. The nonrelativistic wave function, expanded in a basis of exponentially correlated Gaussian functions, yields the lowest upper bounds to the energy of 2 S-1 and 3 S-1 states. By means of the integral representation, a reference-quality Bethe logarithm has been obtained. The resulting theoretical 2 S-1-3 S-1 transition energy amounts to 54 677.78(45) cm(-1) and differs from the known experimental value by about 0.5 cm(-1).
Keywords: beryllium; finite mass; excitation energy